The Geography of R&D; Tobit Analysis and Bayesian Approach to Mapping R&D Activities for The Netherlands - Hans Ouwersloot; Piet Rietveld (Tinbergen Institute, 2000)
Regions vary strongly according to the participation of firms in R&Dactivity.By linking data on R&D activity at thefirm level with GIS based data on economic, and other locationfeatures of zoneswe are able to investigate the impactof local factors on R&D involvement for various types of firms.The relative importance of local factors as determinants of R&Dinvolvement ofthe firms is estimated by means of atobit model. Rather strong differences are found between zones in thesame urbanregion. For example modernmanufacturing firms located in the centre of the large cities haverelativelylow levels of R&D, the opposite holds forrings of zones at a certain distance from the cities. Bayesianmethods are usedfor map presentations of the survey data.
Keywords: 330; R&D; innovation; space; Bayesian approach; Industrieforschung; Räumliche Verteilung; Niederlande